Loss aversion and refund policies - Güçlü, Mehmet Akif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This thesis examines the relationship between loss aversion and refund policy decisions of firms. We consider a two-stage duopoly model with horizontal product differentiation, with and without loss aversion. Firms decide and announce their refund policies simultaneously in the first stage, and then in the second stage they compete in prices in a Hotelling type location model. Discretizing the refund policies as full refund and no refund policies, we analyze the equilibrium refund policies and the prices. On the buyers’ side, they have incomplete information about their true valuation (location) of the product until they buy it, when they realize their true valuation (location). Buyers can return the product and buy from the other firm if the valuation mismatch is sufficiently high and there is an available refund option. We find that there is a price equilibrium for each possible refund policy combination in the absence of loss aversion. In the presence of loss aversion, we find that the set of equilibria can change with the degree of loss aversion, λ. Even though there is a price equilibrium for each possible refund policy combination with small λ, both firms adopting a no refund policy cannot be part of an equilibrium if λ is sufficiently high.
Keywords: Loss aversion.; Economics.